HFIP-mediated three-component imidization of electron-rich arenes with in situ formed spiroindolenines for facile construction of 2-arylspiroindolenines. Issue 6 (14th February 2022) - Ge, Chunyan; Wang, Liang; Hu, Fangzhi; Ding, Zhanshuai; Li, Xinyao; Xiao, Deshuai; Wang, Jiayi; Li, Shuai-Shuai
Abstract : The three-component reaction of o -aminobenzaldehydes with 5-hydroxyindole and electron-rich arenes has been achieved through HFIP-mediated cascade hydride transfer/dearomative cyclization/CDC-type imidization at room temperature under air. Abstract : The three-component reaction of o -aminobenzaldehydes with 5-hydroxyindole and electron-rich arenes has been achieved through HFIP-mediated cascade hydride transfer/dearomative cyclization/CDC-type imidization at room temperature under air, providing a variety of 2-arylspiroindolenines carrying diverse functional groups with moderate to good yields. The derivatizations of the products also were conducted to enhance the synthetic practicality of this protocol.